Phylogenomic study of Orostachys using Angiosperms353: polyphyly of subsections with taxonomic consequences - Lee, Ha-Rim; Kang, Halam; Park, Yoo-Jung; Kwak, Ho-Kwon; Kim, Hyeyeon; Park, Jieun; Choi, Hyeok Jae; Kim, Kyung-Ah; Cheon, Kyeong-Sik (Frontiers in Plant Science, 2025)
IntroductionThe genus Orostachys (Crassulaceae) has been subject to considerable disagreement regarding its taxonomic boundaries because of extensive morphological similarities among taxa and widespread intraspecific variation. Additionally, previous phylogenetic studies based on molecular markers have consistently demonstrated that the two subsections of Orostachys (subsect. Orostachys and subsect. Appendiculatae) do not constitute a monophyletic group, leaving the generic boundaries unresolved to date. Therefore, we aimed to evaluate the generic boundaries and accurate taxonomic positions of individual taxa via the Angiosperms353 target enrichment approach.MethodsWe analyzed a total of 43 individuals representing 25 taxa from 5 genera, including 14 Orostachys taxa and closely related genera such as Hylotelephium and Meterostachys. High-quality genomic data were obtained, with an average gene recovery rate of 99.1% (349.5/353 genes) and substantial sequence length recovery (average 1,223 bp per locus), resulting in concatenated datasets of 397-400 kbp sequences. Phylogenetic analyses using concatenation and coalescent-based approaches with datasets based on different threshold values were conducted.ResultsPhylogenetic analyses revealed exceptionally high concordance across all phylogenetic trees, with most nodes having UFBoot values ≥95% and LPP values ≥0.95. Our findings showed the polyphyletic nature of Orostachys, with O. subsect. Orostachys forming a monophylum distinct from O. subsect. Appendiculatae and related genera. O. subsect. Orostachys constituted a monophyletic group rather than exhibiting a paraphyletic relationship with Hylotelephium. O. ramosa and O. japonica f. polycephala clustered with O. malacophylla and O. japonica, respectively. O. margaritifolia, O. latielliptica, O. chongsunensis, and O. iwarenge f. magnus formed independent clades.DiscussionUnlike previous studies, our Angiosperms353 data demonstrate that O. subsect. Orostachys forms a completely independent lineage, representing the most important finding of this study. The high support values confirm the reliability of our results and demonstrate the effectiveness of the Angiosperms353 approach in resolving complex evolutionary relationships within morphologically challenging plant groups. Our findings support treating O. ramosa and O. japonica f. polycephala as synonyms of O. malacophylla and O. japonica, respectively, while recognizing the endemic Korean species O. margaritifolia, O. latielliptica, O. chongsunensis, and O. iwarenge f. magnus as independent taxa.